Acceso a la información de mujeres con VPH, displasia y cáncer cervical in situ Access to information by women with HPV, cervical dysplasia and cancer in situ - Ma del Carmen Castro-Vásquez; Ma del Carmen Arellano-Gálvez (Salud Pública de México, 2010)
OBJETIVO: Presentar un análisis relacional de cómo mujeres diagnosticadas con el virus del papiloma humano (VPH), displasia del cuello del útero o neoplasias del cuello uterino, reciben y/o acceden a la información y cómo la viven en sus relaciones cercanas. MATERIAL Y MÉTODOS: En 2008 se realizaron 34 entrevistas cualitativas a mujeres en dos clínicas de colposcopía de la Secretaría de Salud, en Hermosillo, Sonora. El análisis se basó en la teoría fundamentada. RESULTADOS: Existe una franca analogía entre cáncer cervicouterino (CaCu) y muerte, una amplia desinformación sobre VPH y displasias y una práctica persistente entre los médicos de no ofrecer información oportuna y clara a las pacientes. Existe una apreciación estigmatizante hacia la infección por VPH que afecta las relaciones cercanas de las mujeres. CONCLUSIÓN: A pesar de la necesidad de las pacientes de obtener información, no la exigen al médico, lo que contribuye a su desconfianza y angustia. OBJECTIVE: To present a relational analysis of how women who are diagnosed with the human papilloma virus (HPV), cervical dysplasia or cervical neoplasia receive or seek information, and how they experience this process within their immediate relationships. MATERIALS AND METHODS: In 2008, 34 qualitative interviews were carried out with women at two Secretary of Health colposcopy clinics in Hermosillo, Sonora. Analysis was based on grounded theory. RESULTS: There is a patent analogy between cervical cancer and death, much disinformation about HPV and dysplasias, and a persistent lack of timely and clear information given to patients by doctors. There is a stigma attached to HPV infection which affects women's immediate relationships. CONCLUSION: Despite patients' need to obtain information, they do not demand it from their doctor, which contributes to their anguish and distrust.